2022
DOI: 10.3389/fgene.2022.846529
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Multiple gastrointestinal perforations in a rare musculocontractural Ehlers–Danlos syndrome with multiple organ dysfunction

Abstract: A 36-year-old male with congenital equinovarus deformity was admitted to the hospital due to worsen deformity. He was known to have ear perforation in childhood. After hospitalization, he received equinovarus correction surgery, fourth toe osteotomy, and external fixation for right foot during the procedure. During his hospital stay, the patient has been treated with multiple gastrointestinal perorations, accompanied with multiple organ dysfunction and fragile soft tissues. During his in-hospital stay, multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Previously reported patients with mcEDS-CHST14 who developed colonic perforation were complicated by diverticula [4], suggesting that diverticula confer susceptibility to perforation, although no clear pathological evidence of this has been identified [4,7,8]. A recently described patient, a 36-year-old male with mcEDS-CHST14, developed colonic perforation at the splenic flexure 11 days after corrective surgery for talipes equinovarus, and underwent an emergency laparotomy plus partial colectomy with proximal fistulotomy [5]. Recovery from subsequent septic shock was achieved through anti-infective therapy, nutritional support, blood transfusion, and mechanical ventilation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously reported patients with mcEDS-CHST14 who developed colonic perforation were complicated by diverticula [4], suggesting that diverticula confer susceptibility to perforation, although no clear pathological evidence of this has been identified [4,7,8]. A recently described patient, a 36-year-old male with mcEDS-CHST14, developed colonic perforation at the splenic flexure 11 days after corrective surgery for talipes equinovarus, and underwent an emergency laparotomy plus partial colectomy with proximal fistulotomy [5]. Recovery from subsequent septic shock was achieved through anti-infective therapy, nutritional support, blood transfusion, and mechanical ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…Ten days after the perforation, he developed a perforation of the gastric antrum, followed by septic shock. Eight days after the gastric perforation, he developed another possible intestinal perforation, complicated by a third septic shock, resulting in multiple organ failure and death [5]. Diverticula were not mentioned, and pathological study showed the infiltration of a large number of inflammatory cells and abscess formation on the first colonic perforation site and inflammatory cell infiltration with fibroblast proliferation in the fibrous connective tissue at the gastric perforation site [5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They proposed to unify the D4ST1-related syndromes, the novel EDS and the adducted thumb-clubfoot syndrome, as "musculocontractural EDS" [143], which was adopted in the International Classification of Ehlers-Danlos Syndromes in 2017 as EDS musculocontractural type 1 [144,145]. In addition to these mutations in CHST14, many probands with EDS musculocontractural type 1 have been reported to date [146][147][148][149][150][151][152][153][154][155][156][157][158][159].…”
Section: Human Genetic Disorders Caused By Mutations In Chst14/d4st1mentioning
confidence: 99%